Forest fragment size and microhabitat effects on palm seed predation - Fleury, M.; Galetti, M. (Elsevier B.V., 2006)
The establishment of plant species depends crucially on where the seeds are deposited. However, since most studies have been conducted in continuous forests, not much is known about the effects of forest fragmentation on the maintenance of abiotic and biotic characteristics in microhabitats and their effects on seed survival. in this study, we evaluated the effects of forest fragmentation on the predation upon the seeds of the palm Syagrus romanzoffiana in three microhabitats (interior forest, forest edge and gaps) in eight fragments of semi-deciduous Atlantic forest ranging in size from 9.5 ha to 33,845 ha in southeastern Brazil. Specifically, we examined the influence of the microhabitat structure, fauna and fragment size on the pattern of seed predation. Fragments < 100 ha showed similar abiotic and biotic characteristics to those of the forest edge, with no seed predation in these areas. Forest fragments 230-380 ha in size did not present safe sites for S. romanzoffiana seed survival and showed high seed predation intensity in all microhabitats evaluated. In fragments larger than 1000 ha, the seed predation was lower, with abiotic and biotic differences among gaps, interior forests and forest edges. In these fragments, the survival of S. romanzoffiana seeds was related to squirrel abundance and interior forest maintenance. Based on these results, we concluded that there are no safe sites for S. romanzoffiana seed establishment in medium- and small-sized fragments as result of the biotic and abiotic pressure, respectively We suggest that on these forest fragments, management plans are needed for the establishment of S. romanzoffiana, such as interior forest improvement and development in small-sized sites in order to minimize the edge effects, and on medium-sized fragments, we suggest post-dispersal seed protection in order to avoid seed predation by vertebrates. our findings also stress the importance of assessing the influence of forest fragmentation on angiosperm reproductive biology as part of the effective planning for the management of fragmented areas. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Arecaceae; habitat fragmentation; edge effects; microhabitat; seed predation; sciurus